2011
DOI: 10.5946/ce.2011.44.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Current Advance in Small Bowel Tumors

Abstract: Small intestinal tumors are difficult challenge to gastroenterologists. The difficulty in making a diagnosis of small intestinal tumor lies in the relative inaccessibility and absence of typical presentation. New endoscopic and radiologic technologies provide clear and fine anatomical visualization of the small bowel and are approved to improve the diagnostic sensitivity and accuracy. Patients at risk of small intestinal tumors might gain a benefit from proper surveillance with this new technology. Minimally i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 76 publications
0
29
0
Order By: Relevance
“…Compared to sporadic SBA in general population, patients with LS present a decade earlier. About 10% of patients develop cancers before the age of 30 [27] . The lifetime risk for SBA is estimated as 1%-4% and is greater than 100 fold risk compared to general population [13,14,28] .…”
Section: Lynch Syndromementioning
confidence: 99%
“…Compared to sporadic SBA in general population, patients with LS present a decade earlier. About 10% of patients develop cancers before the age of 30 [27] . The lifetime risk for SBA is estimated as 1%-4% and is greater than 100 fold risk compared to general population [13,14,28] .…”
Section: Lynch Syndromementioning
confidence: 99%
“…The utilization of double contrast method of enteroclysis has increased the detection sensitivity to almost 90%; however, it is only used in 50 to 60% patients being evaluated for SB pathology due to limitations such as lack of visualization of a luminal lesion and the need for a highly-skilled radiologist. 23 CT enteroclysis (CTE) has become a superior modality for the evaluation of SBC because it allows the exploration of the entire SB as well as extraintestinal involvement. CTE can detect SBC that are only 5 mm in size with a negative and positive predictive value for SBC of 100 and 94.7% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13] Unfortunately, when overt symptoms are present, there may be local invasion or metastases of the tumor, portending a poor prognosis. 3 …”
Section: Clinical Presentation Of Patients With Small-bowel Tumorsmentioning
confidence: 97%
“…Now, with the development of video capsule endoscopy, as well as deep enteroscopy, that is, balloon-assisted enteroscopy and spiral enteroscopy (SE), the reported incidence of small-bowel tumors has increased. This was reflected in a 2012 Korean study 3 in which the incidence of small-bowel tumors evaluated by capsule endoscopy (CE) had risen to 4.3%; another study 4 identified small-bowel tumors in 8.9% of patients. These studies suggest that the incidence of small-bowel tumors may be higher than previously thought.…”
mentioning
confidence: 95%